Getting back on track after treatment of cancer: A qualitative interview study of cancer survivors' experiences. - Doris van der Smissen; Marjolein Lugtenberg; Manon Enting; Laurens Beerepoot; Floortje Mols; Evelien Brouwers; Dareczka Wasowicz; Margot Joosen (PLoS ONE)
Objective An increasing number of people resumes life after cancer treatment. Although the (long-term) side-effects of cancer and its treatment can be significant, less is known about the impact on cancer survivors' participation in daily life. The aim of this study was to explore the common experiences of cancer survivors in resuming life after treatment. Methods A semi-structured interview study was conducted among 22 cancer survivors having a favorable prognosis after treatment. Purposive sampling was used to select a variable sample in terms of diagnoses (e.g. breast cancer, colorectal cancer, melanoma), age (18-77 years), and time after diagnosis (0-7 years). Interviews were audio-taped, transcribed verbatim and analyzed in a thorough thematic analysis. Results Four main themes were identified. First, cancer survivors reported an emotional fallout episode to often follow treatment, which was characterized by a loss of direction and control due to discontinuation of medical care, decreased support from healthcare professionals and their social network, and an emotional set back. Second, survivors experienced challenges with getting back on track such as the impact of impaired physical and cognitive functions, and challenges and uncertainty related to work and finances. Third, in coping with changes and regaining trust they tried to find a balance between dealing with patient stigma and fear of recurrence on the one hand, and maintaining a positive mindset on the other hand. Fourth, the disease often led to re-evaluating values in life, health and work, which included realizing and accepting change and having a more conscious outlook on life. Conclusion In resuming life after treatment, cancer survivors experience several challenges and changes in values in different life domains that extend beyond the specific diagnosis. To improve supportive care, healthcare professionals should focus on the (changed) individual needs and values of survivors in the domains considered relevant to them.